Controlling the dispersion of supported polyoxometalate heterogeneous catalysts: impact of hybridization and the role of hydrophilicity–hydrophobicity balance and supramolecularity - Raj, Gijo; Swalus, Colas; Arendt, Eglantine; Eloy, Pierre; Devillers, Michel; Gaigneaux, Eric M (Beilstein journal of nanotechnology, 2014)
The hybridization of polyoxometalates (POMs) through an organic–inorganic association offers several processing advantages in the design of heterogeneous catalysts. A clear understanding of the organization of these hybrid materials on solid surfaces is necessary to optimise their properties. Herein, we report for the first time the organization of Keggin phosphotungstic [PW 12 O 40 ] 3− and Wells–Dawson (WD) phosphomolybdic [P 2 Mo 18 O 62 ] 6− anions deposited on mica (hydrophilic), and highly oriented pyrolytic graphite (HOPG) (hydrophobic) surfaces. Next, the supramolecular organization of the organic–inorganic hybrid materials formed from the association of POM anions and dimethyldioctadecylammonium bromide (DODA) is investigated as a function of the hydrophilic or hydrophobic nature of the surfaces. The height of the Keggin-POM anions, measured with tapping mode (TM-AFM) is always in good agreement with the molecular dimension of symmetric Keggin-POM anions (ca. 1 nm). However, the asymmetric WD-POM anions form monolayer assemblies on the surfaces with the orientation of their long molecular axis (ca. 1.6 nm) depending on the hydrophilic or hydrophobic properties of the substrate. Namely, the long axis is parallel on mica, and perpendicular on HOPG. When hybridized with DODA, the organization of the hybrid material is dictated by the interaction of the alkyl side chains of DODA with the substrate surface. On HOPG, the DODA–POM hybrid forms small domains of epitaxially arranged straight nanorod structures with their orientation parallel to each other. Conversely, randomly distributed nanospheres are formed when the hybrid material is deposited on freshly cleaved mica. Finally, a UV–ozone treatment of the hybrid material allows one to obtain highly dispersed isolated POM entities on both hydrophilic and hydrophobic surfaces. The hybridization strategy to prevent the clustering of POMs on various supports would enable to develop highly dispersed POM-based heterogeneous catalysts with enhanced functionalities.